Incidence of Molds on Pecan Nuts at Different Points During Harvesting - Beuchat, L. R. (1975)
Pecan nuts were selected at various points during routine harvesting, and nutmeats were analyzed for gross and internal fungal contamination and for the presence of Aspergillus flavus and A. parasiticus. Fungi were isolated from a large percentage of the nutmeats at all points of examination. No correlations could be made between increased incidence of fungi and particular harvesting procedures.